Exposure to nature during the COVID-19 pandemic and the associated effect on mental health: a systematic review with meta-analysis. (October 2022) - Patwary, Muhammad Mainuddin; Dzhambov, Angel; Disha, Asma Safia; Bardhan, Mondira; Haque, Md Zahidul; Rahman, Md Atiqur; Tareq, Md Faysal; Browning, Matthew H E M; Larson, Lincoln R; Alam, Md Ashraful; Labib, S M; Shuvo, Faysal Kabir; et al.
Abstract: Background: The COVID-19 pandemic and measures such as lockdowns to control its transmission generated unique effects on psychological health and well-being. In these circumstances, access to nature and outdoor spaces became a potentially important coping strategy, but the evidence exploring the mental health benefits of nature exposure during different stages of the pandemic is mixed and poorly understood. We systematically synthesised the evidence to examine larger trends in associations between nature exposure and mental health during the COVID-19 pandemic. Methods: We did a comprehensive keyword search in PubMed, Web of Science, Scopus, CINAHL, and PsycInfo for articles published between Jan 1, 2020 and April 30, 2022. We followed the PRISMA guidelines to synthesise and report results. Using the Navigation Guide systematic review methodology, we established the risk of bias in studies at the individual level and throughout the body of evidence for each outcome of interest. Findings: A total of 2004 relevant articles were initially identified and after screening for relevancy, 72 were included in the review. Studies found associations between green space visit frequency, green space accessibility, and type of green space (eg, indoor vs outdoor) with mental health outcomes (eg, depression and anxiety) during the pandemic. However, evidence for links between satellite image-driven measures of greenness (eg, normalised difference vegetation index) and mental health was scarce. Meta-analysis shows that access to gardens was associated with lower odds of depression (odds ratio 0·71, 95% CI 0·61–0·82, I 2 =0%) and anxiety (0·73, 0·63–0·84, I 2 =0%). Similarly, higher frequency of visits to green space was associated with improved mental wellbeing (0·10, 95% CI 0·07–0·14, I 2 =0%) and general mental health (0·11, 95% CI 0·03–0·38, I 2 =82%). Interpretation: Interventions that prioritise nature-based infrastructure and emphasise exposure to nearby nature (eg, indoor plants or gardens), and visits to green spaces such as parks, could create more psychologically resilient communities in the face of future public health crises. Funding: None.